2005
DOI: 10.1086/502539
|View full text |Cite
|
Sign up to set email alerts
|

A Large Outbreak ofClostridium difficile–Associated Disease with an Unexpected Proportion of Deaths and Colectomies at a Teaching Hospital Following Increased Fluoroquinolone Use

Abstract: Exposure to levofloxacin was an independent risk factor for C. difficile-associated diarrhea and appeared to contribute substantially to the outbreak. Restricted use of levofloxacin and the other implicated antibiotics may be required to control the outbreak

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
371
4
14

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 584 publications
(404 citation statements)
references
References 48 publications
15
371
4
14
Order By: Relevance
“…As many risk factors for CDI are correlated, multivariate analysis provides independent risk estimates for variables that occur at the same time. Most multivariate models fi nd advanced age, antibiotic use, co-morbidities, and longer hospital stays are independently predictive of CDI ( 211,214,232 ). Although several studies have not shown an association with proton pump inhibitors (PPIs) and CDI, many other studies have found an association ( 235,236 ).…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…As many risk factors for CDI are correlated, multivariate analysis provides independent risk estimates for variables that occur at the same time. Most multivariate models fi nd advanced age, antibiotic use, co-morbidities, and longer hospital stays are independently predictive of CDI ( 211,214,232 ). Although several studies have not shown an association with proton pump inhibitors (PPIs) and CDI, many other studies have found an association ( 235,236 ).…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Because there are few published data on the performance of one of the PCR tests, Simplexa -C. diffi cile Universal Direct Test (Quest Diagnostics, Madison, NJ), and the ribonuclease-mediated isothermal amplifi cation and chip-based detection method test (Great Basin Corporation, Salt Lake City, UT), it is not possible to comment on their performance at this time. Meta-analysis of three commercial PCR assays, GeneOhm Cdiff Assay BD Diagnostics GeneOhm, San Diego, CA; Xpert C. diffi cile Test Cepheid, Sunnyvale, CA; and ProGastro Cd Assay Gen-Probe, San Diego, CA indicate that they have similar sensitivities of and specifi cities of ~ 90 % and ~ 95 % , respectively, compared with TC ( 214 ). A recent large study comparing widely used commercially available tests showed that PCR for toxigenic C. diffi cile and GDH testing were the most sensitive tests for detection of C. diffi cile in stool specimens compared with a composite reference method of TC or a negative culture in patients with multiple positive tests and a clinical course consistent with CDI.…”
Section: Microbiological Testingmentioning
confidence: 99%
“…En 2001, Fernández-Caniggia, et al, (24) reportaron la edad avanzada, las comorbilidades, la hospitalización, el tratamiento antimicrobiano y la inmunosupresión reciente, como factores asociados a la infección por C. difficile en una serie de 245 pacientes en Argentina (25). En México, en un estudio de 113 casos y 226 controles, CamachoOrtiz, et al, encontraron que la edad de más de 65 años, el uso de inhibidores de la bomba de protones, la hospitalización durante las 12 semanas previas al diagnóstico, la hospitalización prolongada, la estancia en la unidad de cuidados intensivos y el uso previo de antibióticos, eran factores de riesgo para la infección por C. difficile (26).…”
Section: Discussionunclassified
“…424,425 Although alcohol-based handrubs may not be effective against C. difficile, it has not been shown that they trigger the rise of C. difficile-associated disease. [426][427][428][429] C. difficile-associated disease rates began to rise in the USA long before the wide use of alcohol-based handrubs. 430,431 One outbreak with the epidemic strain REA-group B1 ( ribotype 027) was successfully managed while introducing alcohol-based handrub for all patients other than those with C. difficile-associated disease.…”
Section: Activity Of Antiseptic Agents Against Sporeforming Bacteriamentioning
confidence: 99%